IMPROVING STUDENTS’ SPEAKING SKILLS BY USING AUDIO-VISUAL TECHNOLOGY - Rumondor, Yesaya Gabriel Baginda; Liando, Nihta V. F.; Maukar, Merlin M. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
This research discovered the Audio-visual technology as a media to improve speaking skills specifically in speech accuracy and fluency, increase students’ knowledge and provide opportunities for to SMP Kristen Koka IX grade students to demonstrate their speaking skills. This research involves teaching video that are consistent with the SMP Kristen Koka IX grade class curriculum with a projector and loudspeaker operating K13 by fulfilling KI, KD, and achievement indicators that were set. The data in this research be collected by using rubric scoring accuracy and fluency to discover students’ speaking skills. The results students’ mastery was taken from the post-test, The mean post-test score is 6.5 for accuracy and 8.35 for fluency. The greatest accuracy score is nine (9) acquired by five (5) students, and the lowest is eight (8) achieved by eleven (11) students, while the highest fluency score is nine (9) achieve by one student and lowest fluency score is six (6) achieved by seven (7) students. The data revealed that some students' scores improved significantly, but their pre-test scores were poor due to their inability to convey ideas during the teaching learning process. So, in this study, the use of audio-visual technology as a teaching and learning medium can increase students' speaking skills by improving their thinking and allowing them to readily absorb knowledge from the audio-visual and apply it to their speaking skills.